REMOTE WORK AND DIGITAL TECHNOLOGIES IN HEALTHCARE: IMPLICATIONS FOR HEALTHCARE WORKERS’ MENTAL WELLBEING – A NARRATIVE REVIEW - Jakub Minas; Paulina Dybiak; Maciej Zachara; Mateusz Bartoszek; Patryk Harnicki; Erwin Grzegorzak; Oliwia Krawczyk; Adrian Morawiec; Paweł Słoma; Rafał Pelczar; Mikołaj Grodzki (International Journal of Innovative Technologies in Social Science, 2026)
The rapid expansion of remote work and digital technologies has significantly transformed healthcare systems, particularly following the COVID-19 pandemic. While telework and digital tools have enabled continuity of care and organisational flexibility, their implications for healthcare workers’ mental wellbeing remain insufficiently synthesised. Healthcare workers constitute a professional group highly exposed to occupational stressors, including high workload, emotional demands, and moral distress, which may be exacerbated or alleviated by digitalised work arrangements. The aim of this narrative review is to synthesise current evidence on the impact of remote work, telemedicine, and digital mental health interventions on the psychological wellbeing of healthcare workers and to identify key moderating factors influencing these outcomes. A structured literature search was conducted in PubMed and the Cochrane Library, including systematic reviews, observational studies, and intervention trials published in English. Findings indicate that remote work and telemedicine may offer benefits such as increased job flexibility, reduced infection risk, and improved efficiency, which can positively affect mental wellbeing when appropriately implemented. However, adverse outcomes, including social isolation, digital fatigue, blurred work–life boundaries, and increased cognitive load, are frequently reported, particularly in contexts of inadequate organisational support. Digital mental health interventions show potential for reducing stress and improving coping skills, although evidence of long-term effectiveness remains limited. Overall, the psychological impact of digitalised work in healthcare is highly context-dependent. Organisational policies that prioritise autonomy, training, workload management, and supportive digital infrastructures are essential to maximise benefits and mitigate risks for healthcare workers’ mental wellbeing.